Design of a PV‐fed Electric Vehicle Charging Station with a Combination of Droop and Master‐Slave Control Strategy - Krishnan Nair, D; Prasad, K; Lie, TT (Wiley, 2023)
Electric vehicles (EVs) are becoming essential elements for both the transport and power sectors. Consequently, they need a suitable charging infrastructure at the same time. Electric vehicle charging stations (EVCS) assisted by photovoltaic (PV) panels draw attention due to minimal expenditure, increased environmental awareness, and a consistent increase in the effectiveness of the PV modules. In this paper, a combination control scheme utilizing the merits of both droop and master-control strategies for the EVCS is proposed. In addition, an isolated bidirectional DC-DC converter combined with the snubber circuits and a three-level boost converter that utilizes a capacitance-voltage control design is used to further enhance the system stability. The design of the EVCS is formulated and validated through MATLAB/Simulink.
Keywords: bidirectional converter; droop control; electric vehicle charging station; master-slave control; photovoltaic; snubber circuit